A time–temperature–moisture concentration superposition principle that describes the relaxation behavior of epoxide molding compounds for microelectronics packaging. Issue 6 (17th July 2020) - Huber, Fabian; Etschmaier, Harald; Walter, Hans; Urstöger, Georg; Hadley, Peter
Abstract: Time–temperature superposition is a well-established principle used in the constitutive description of viscoelastic polymers. To expand the description to moisture-induced plasticization effects, two epoxide-based molding compounds used in microelectronics packaging were characterized by dynamic mechanical analysis under varying temperature and moisture controlled environments in their glassy regime. Conditions of up to 85 °C and 85% relative humidity, relevant for industry-defined reliability standards, were applied. By relating the transient ambient conditions to the actual moisture concentration of the samples, temperature-, and moisture concentration-dependent relaxation functions were obtained. By applying a time–temperature–moisture concentration superposition, it is shown, that the materials' behavior can be described assuming a linear dependence of the relative free volume on both temperature and concentration. The two parameters can be super-positioned in the description of the shift of the relaxation time constant spectrum with negligible cross-correlation for the conditions of industrial interest.